2014
DOI: 10.1504/ijatm.2014.065291
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of carsharing diffusion in Germany: an actor-centred approach

Abstract: Carsharing increasingly gains ground as a transportation mode in Europe and the world. The present paper contributes to the literature by studying the roles and interplay of market and non-market actors in the diffusion of carsharing. It applies an actor-centred framework to the context of market development of carsharing in Germany, considering the perspectives of carsharing providers, customers, and politics. Data from secondary sources, national published printed matters, and survey data are used to analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 39 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…The benefits of car sharing that might appeal to users are convenience aspects [56]. Convenience aspects like flexibility, time and effort savings on finding parking spots, and simple pricing systems have a positive effect on attitude toward car sharing services [21]. The semi-structured interview results also revealed that convenience was of importance as the main driver of deciding and choosing to use car sharing.…”
Section: Hypotheses Formulation Based On the Semi-structured Interviementioning
confidence: 98%
See 2 more Smart Citations
“…The benefits of car sharing that might appeal to users are convenience aspects [56]. Convenience aspects like flexibility, time and effort savings on finding parking spots, and simple pricing systems have a positive effect on attitude toward car sharing services [21]. The semi-structured interview results also revealed that convenience was of importance as the main driver of deciding and choosing to use car sharing.…”
Section: Hypotheses Formulation Based On the Semi-structured Interviementioning
confidence: 98%
“…Other benefits of car sharing may include the cost-saving advantages. Car sharing can be profitable for users who sometimes use a car for short trips [21]. It can provide users with monetary advantages compared to expenses of private car ownership [70].…”
Section: Hypotheses Formulation Based On the Semi-structured Interviementioning
confidence: 99%
See 1 more Smart Citation
“…The promises of carsharing has attracted research interests. So far, most publications on carsharing have focused on the question which consumers opt for carsharing and why they do so (Burkhardt & Millard-Ball, 2006;Juschten, Ohnmacht, Thao, Gerike, & H€ ossinger, 2017;Lindloff, Pieper, Bandelow, & Woisetschl€ ager, 2014;Martin et al, 2010;Schaefers, 2013;Sioui et al, 2013). And, in transportation research more specifically, there is also work on ondemand modeling and the logistic optimization of carsharing systems [for reviews, see Ciari, Balac, & Axhausen (2016) and Vosooghi, Puchinger, Jankovic, & Sirin (2018)].…”
Section: Introductionmentioning
confidence: 99%
“…Although privately owned cars dominate personal transport today, this may shift as a consequence of changing behaviour and official policies on energy efficiency and pollution reduction (Lanzini, 2018). At the same time, car sharing is gaining momentum worldwide (Lindloff et al, 2014;Shaheen and Cohen, 2013).…”
Section: Introductionmentioning
confidence: 99%